THE IMPLEMENTATION OF PROJECT BASED LEARNING TO PROMOTE STUDENTS’ MOTIVATION IN EFL WRITING CLASS - Eva Fitriani Syarifah (ENGLISH EDUCATION DEPARTMENT - UNIVERSITAS SINGAPERBANGSA KARAWANG, 2018)
One of the problems in writing class is less of students’ motivation. To promote students’ motivation in writing, the researcher tries to implement Project Based Learning (PBL). This research focus on the implementation of PBL, steps by steps in writing class, as well as if it affects students’ motivation in writing. This research employed case study research design. The data were gathered through teaching program and interview. The results show that there are three main parts in implementing PBL which consist of planning, creating, and processing. Moreover, the students felt motivated in writing through PBL.